Passion for entrepreneurship or passion for the product? A conjoint analysis of angel and VC decision-making - Warnick, Benjamin J.; Murnieks, Charles Y.; McMullen, Jeffery S.; Brooks, Wade T. (Journal of Business Venturing, 2018)
Passion is important to venture investors, but what specifically do they want entrepreneurs to be passionate about? This study theorizes that angel investors and venture capitalists consider both entrepreneurs' passion for activities related to the product or service the venture provides (i.e., product passion) and passion for founding and developing new ventures (i.e., entrepreneurial passion). We demonstrate that both types of passion become more appealing when the investor perceives that the entrepreneur is highly open and receptive to feedback, suggesting that openness to feedback mitigates potential concerns associated with passion in its extremes. We further find that venture investors differ in their consideration of passion; angel investors and venture capitalists with more investing experience place greater emphasis on the combination of product passion and openness to feedback, whereas those with more entrepreneurial experience emphasize the combination of entrepreneurial passion and openness to feedback.